Giant Intracranial Pial Arteriovenous Fistula Treated by Endovascular Intervention - de Aguiar, G. B.; Conti, M.L. M.; Veiga, J.C. E.; Jory, M. (min - Minimally Invasive Neurosurgery, 2011)
Arteriovenous fistulas (AVF) are rare vascular lesions of the brain that differ from arteriovenous malformations as they present a direct connection between artery and vein, without interposition of the nidus. They are fed by one or more arterial branches, with a single draining vein. Clinically they can be revealed through cerebral hemorrhage, convulsive crisis, neurological deficit, heart failure in neonates and infants, headache, bruit, or intracranial hypertension symptoms.A 30-year-old patient was found unconscious on a public street, presenting a generalized tonic-clonic convulsive crisis. At admission, she presented with ocular proptosis, conjunctival hyperemia and bilateral jugular turgescence. The cranial computed tomography showed diffuse subarachnoid hemorrhage, and the cerebral angiography evidenced a giant intracranial pial AVF with high flow supplied by 2 branches of the left anterior cerebral artery.The patient underwent endovascular treatment in 2 sessions, using a mixture of histoacryl and lipiodol for complete occlusion of the lesion. She was discharged after a month, alert, devoid of motor deficit, and the ocular proptosis and the conjunctival hyperemia had decreased.AVFs are rare vascular lesions that require prompt treatment. The endovascular treatment must be considered, especially when the lesions are deep and the risks of neurological deficit associated with the surgery are high. Endoscopic intervention represents an effective and safe option for the treatment of this type of lesion.
Keywords: arteriovenous malformation; subarachnoid hemorrhage; vascular malformation; endovascular treatment